The Nature of Racial Microaggressions in White Adults: A Community Sample Validation of the Cultural Cognitions and Actions Scale - Parigoris, Ryan (Race and social problems, 2025)
The Cultural Cognitions and Actions Scale (CCAS) is an established self-report measure of White individuals’ microaggressive likelihood against Black people consisting of four subscales: Negative Attitudes, Colorblindness, Objectifying, and Avoidance. To replicate and address limitations of previous studies, the current study sought to validate the CCAS with a geographically diverse sample of White U.S. adults (N = 254) who completed a battery of measures of explicit and implicit racial bias, administered online with Amazon Mechanical Turk. A series of hierarchical multiple regressions assessing predictors of each individual item and subscale (except for Objectifying) provides evidence for concurrent validity with regard to measures of colorblindness (Colorblindness subscale, adjusted R2 = 0.47), allophilia, old-fashioned and modern racism (Negative Attitudes subscale, adjusted R2 = 0.52), and intergroup anxiety (Avoidance subscale, adjusted R2 = 0.29). Furthermore, partial correlations controlling for social desirability found that the CCAS scales did not significantly correlate to implicit racial bias as measured by the IAT, though they did relate to higher levels of aggression (r range: 0.26 to 0.30), lower implicit motivation to respond without prejudice (r range: − 0.27 to − 0.51), and higher levels of political conservatism (r range: 0.29 to 0.51). This research further supports the notion that common verbal racial microaggressions may be expressions of well-understood, racist and racially biased, psychological processes.